3d+3d+3d-9d=12

Simple and best practice solution for 3d+3d+3d-9d=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3d+3d+3d-9d=12 equation:


Simplifying
3d + 3d + 3d + -9d = 12

Combine like terms: 3d + 3d = 6d
6d + 3d + -9d = 12

Combine like terms: 6d + 3d = 9d
9d + -9d = 12

Combine like terms: 9d + -9d = 0
0 = 12

Solving
0 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 12=0.005w | | 9/6=15/2 | | 4(s-7)+6(a-23)=14 | | 4(x-6)=117 | | 16v+14v+-18v=-12 | | 2x-17=2x-3 | | 2n^2+3m^2=40 | | 1/8(16x-24) | | 4(x-6)=39 | | 19w-w-14w+4w-6w=20 | | 16-4x=3x-12 | | 6x=-15x | | 2x-17+2x-3=180 | | 4/7p=-12/11 | | 30p^2-30-11p=0 | | x(y-6)=y+4 | | 47-5x=3x-7 | | -2.9-2x=-0.3 | | 8-2t=1t+17 | | 166=-8(-6+7r)-3r | | 15/tan25=x | | -2.9-2x=0.3 | | 2(5X+9)=3(4X+7) | | 2(3x^2+3)-(x^2-5x+7)= | | -7(2-6)=70 | | (6-x)=30 | | (4a-3)(a+4)=0 | | 1x-2y=-4 | | a-18=54 | | g+4.5=12 | | 2/3(8a-15)=7/9 | | 18-2(7-4)= |

Equations solver categories